PROPOSAL OF A SYNTHETIC IND ICATOR TO CONTROL ECOLOGICAL DYNAMICS AT AN ECOLOGICAL MOSAIC SCALE - INGEGNOLI, V.; GIGLIO, E. (Annali di Botanica, 1999)
The problem to control transformations of an ecological mosaic is becoming more and more important. These transformations occur according to processes linked with thresholds of metastability, which correspond to a passage from a metastable equilibrium to another. Trying to evaluate the metastability of a certain ecological mosaic, it is necessary to identify the levels of replacement and to measure the metastability of each element, in order to consider their complementarity. It is possible to measure the capacity of an ecological mosaic, formed by a vegetational mosaic, defining a synthetic quantity, named biological territorial capacity, or Btc. It ranks landscape’s elements, giving high values to high-resistance ecosystems. Therefore, it is possible to use the Btc as a synthetic indicator of the metastability of an ecological mosaic. Some examples of application regard Gallarate heath-land (local scale) and Lathium, Lombardy and Sicily (regional scales).